Pengaruh Strategi Mengajar Guru Terhadap Pemahaman Siswa Pada Mata Pelajaran Ekonomi di SMA Negeri 2 Tilamuta - Febriyanto Mahmud; Sri Endang Saleh; Maya Novrita Dama; Frahmawati Bumulo; Rierind Koniyo (Yayasan Pendidikan Sudirman Mandiri, 2026)
This study aims to determine the effect of teacher teaching strategies on student understanding at SMA Negeri 2 Tilamuta Gorontalo. The research question is whether teacher teaching strategies influence students' level of understanding during the learning process. The study employed a quantitative approach with a survey method. The sample size was 30 students selected using proportional random sampling. Data were collected through observation, questionnaires, and documentation, then analyzed using simple linear regression with IBM SPSS Statistics version 21. The results showed that teacher teaching strategies had a positive and significant effect on student understanding, as indicated by a calculated t-value of 3.073, which is greater than the t-table of 2.04841, and a significance value of 0.005 <0.05. Therefore, the better the teaching strategies implemented by teachers, the higher the level of student understanding of the learning material.